Aspirin-free strategies in cardiovascular disease and cardioembolic stroke prevention - Capodanno, Davide; Mehran, Roxana; Valgimigli, Marco; Baber, Usman; Windecker, Stephan; Vranckx, Pascal; Dangas, George; Rollini, Fabiana; Kimura, Takeshi; Collet, Jean-Philippe; Gibson, C Michael; Steg, Philippe Gabriel; et al. (Nature reviews cardiology, 2018)
In patients with manifestations of cardiovascular disease, acetylsalicylic acid (popularly known as aspirin) has been the mainstay of treatment for decades owing to its capacity to reduce the risk of ischaemic events. Accordingly, novel antithrombotic therapies have been traditionally tested on a background of acetylsalicylic acid therapy. Although the adjunctive use of such antithrombotic therapies can potentially further reduce the risk of ischaemic events, these agents are also inevitably associated with an increased risk of bleeding. However, acetylsalicylic acid also increases the risk of bleeding, challenging the paradigm that this agent should remain the cornerstone of antiplatelet treatment when alternative antithrombotic agents are also used. Many antithrombotic compounds are characterized by increased potency and consistent efficacy, which might lessen the need for concomitant acetylsalicylic acid. Accordingly, numerous investigations are testing the hypothesis that acetylsalicylic acid-sparing regimens based on newer antithrombotic agents might have an increased net benefit for individual patients owing to the reduction in bleeding risk, without a trade-off in efficacy. This Review summarizes the state of the art relating to antithrombotic approaches with and without acetylsalicylic acid for the prevention of cardiovascular disease and cardioembolic stroke. Discussion of the scientific rationale, from bench to bedside, for ongoing studies of acetylsalicylic acid-free pharmacological strategies is included.